A trust model for distributed systems based on reputation. (19th December 2005) - Derbas, Ghada; Kayssi, Ayman; Chehab, Ali; Artail, Hassan, Ayman Tajeddine
Due to the endless attempts at breaching the security of distributed systems, it has become a necessity to investigate an entity's trustworthiness and reliability before interacting with it. The ideal solution is to have a trusted environment, but since this is impractical, efforts have focused on devising frameworks for computing trust through reputation. This paper presents a reputation-based trust model that allows hosts in distributed systems to protect their resources from other malicious hosts. This model is unique in being a truly comprehensive model since it accounts, in a unified framework, for a multitude of concepts such as prior-derived reputation, first impression, loss of reputation information with time, hierarchy of host systems (neighbours, friends, and strangers), and the inclusion of interaction results in reputation calculation. We show both the simulation and implementation results that verify the correctness of this model and the effects of its various model parameters.